Practical predictive analytics and decisioning systems for medicine : informatics accuracy and cost-effectiveness for healthcare administration and delivery including medical research - Winters-Miner, Linda A.; Winters-Miner, Linda A.; Bolding, Pat S.; Hilbe, Joseph M.; Goldstein, Mitchell; Hill, Thomas; NIsbet, Robert; Walton, Nephi; Miner, Gary D. (Academic Press, 2015)
Of Royal Decrees Of Medical Documentation in Ancient CulturesEffects of the Middle Ages on Medical Documentation; Rebirth of Interest in Medical Documentation During the Renaissance; The Printing Press; The Protestant Reformation; Erasmus; Human Anatomy; Andreas Vesalius (1514-1564); William Harvey (1578-1657); Medical Documentation Since the Enlightenment; Medical Case Documentation; The Development of the US National Library of Medicine; Part 2: Analytical and Decision Systems in Medicine and Health Care; Computers and Medical Databases; Medical Databases.